TOYS, PLAY, AND CHILD DEVELOPMENT (Editor: Jeffrey H. Goldstein) - Allan, John (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1995)
Jeffrey H. Goldstein (Editor). TOYS, PLAY, AND CHILD DEVELOPMENT. Cambridge, England; New York, NY; Melbourne, Australia: Cambridge University Press (1994). 189 pp., 49.95 (hardcover), 14.95 (paper). ISBN 0-521-45062-4 & 45564-2.